Analisis kekasaran hasil pembubutan material aluminium dengan menggunakan pahat HSS dan carbide pada mesin CNC - Badaruddin Anwar; Anwar Fatah (Seminar Nasional LP2M UNM, 2019)
This study aims to determine the differences in the roughness of the results of turning aluminium material with using HSS and carbide tool on CNC machines. This research consists of two samples, namely turning of aluminium material using HSS chisels which amounted to 3 samples and carbide chisels which amounted to 3 samples on a CNC machine. There are significant differences in the roughness of the results of turning aluminium material using HSS and carbide tools. The difference is Ra= 0.361, Rq= 0.389, Rz= 0.223. This difference proves that the results of aluminium turning using a carbide tool are finer than using an HSS tool.